Recruiting learners' musical games as resources for South African music education, using a multiliteracies approach - Harrop-Allin, Susan (My University, 2010)
ABSTRACT This thesis investigates the development of learner-centred teaching in South African music education by exploring the possibilities that children‟s musical games offer for pedagogy. Within the broader context of the complexities, challenges and constraints in Arts and Culture education implementation, it proposes that the Multiliteracies theoretical and methodological framework facilitates learner-centred teaching because it „recruits‟ learners‟ situated cultural practices as potential resources for pedagogy. Thus a Multiliteracies approach can be applied productively to music education in order to transform teaching and learning. This research also advocates utilising aspects of ethnography in music education. An ethnographic approach is used to analyse the musical, cultural and social content and value of township children‟s musical games, and how these games constitute children‟s musical situated practices. Ethnographic methods are used to describe and interpret such games, and it is proposed that ethnography brings to music education a deeper understanding of musical forms and practices in their socio-cultural context. It is argued that ethnographic research is necessary prior to embarking on the pedagogy of recruitment central to the Multiliteracies approach. It is proposed that children‟s games are valuable resources that may be recruited for formal teaching and learning. The primary thesis is that the Multiliteracies pedagogical framework provides a methodology for incorporating and developing learners‟ musical practices in music education. This proposal is tested in three case studies working with Arts and Culture teachers in Soweto primary schools. The process of applying a Multiliteracies pedagogical innovation to music education was observed and recorded in these schools, in order to investigate the dialogue between curriculum implementation and learners‟ embodied musical practices. The thesis finds that a Multiliteracies approach can be applied effectively to music education, given particular school conditions and the presence of an artistic sensibility in Arts and Culture teachers. It concludes that, despite the constraints of the present South African education system, adopting innovative pedagogies such as the Multiliteracies approach enables teachers to use their learners‟ musical practices productively in ways that promote transformative learning. Thus this research contributes both to music education and to the Multiliteracies endeavour, and promotes a closer relationship between the epistemological assumptions and methods of ethnomusicology and music education.